Field notes contributed by Dennis Thompson, fall 1996 - Thompson, Denniset al (1996)
List of birds and locations contributed by Dennis Thompson. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1996. Epson - sheet feed